Green Synthesis of Silver Nanoparticles by Boucerosia procumbens (Gravely & Mayur.) - Prakash, Janetha D Prakash; Samuel P, David (International Journal of Applied Sciences and Biotechnology, 2017)
The aim of this study was to synthesis of Silver Nanoparticles in the ethanol extract of Boucerosia procumbens. Nanoparticles are being used in many commercial applications. The synthesized Silver Nanoparticles were characterized by SEM (Scanning Electron Microscopy). It was found that ethanol silver iron can be reduced by ethanol plant extracts of plant to generate to extremely stable Silver Nanoparticles. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 168-171